2014
DOI: 10.1016/j.crvasa.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular twist in isolated left ventricular noncompaction

Abstract: c o r e t v a s a 5 6 ( 2 0 1 4 ) e 4 7 1 -e 4 7 7Left ventricle twist Isolated left ventricular noncompaction a b s t r a c tThe study aimed at assessing the rotational motion of the left ventricle around the long axis in patients affected by isolated left ventricular noncompaction (LVNC) and comparing their results with those of healthy volunteers. Patients and methods: The study comprised eight patients with LVNC confirmed by echocardiography and magnetic resonance imaging (mean age 41 AE 19 years; four mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…The absence of a significant difference in LV twist and torsion is inconsistent with previous STE studies demonstrating significantly decreased twist in LVNC phenotype patients compared to healthy subjects [17,18]. A disadvantage of CMR FT compared to STE that may partly account for these differences is the fairly uniform water content and thus homogenous signal within myocardium on bSSFP sequences.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…The absence of a significant difference in LV twist and torsion is inconsistent with previous STE studies demonstrating significantly decreased twist in LVNC phenotype patients compared to healthy subjects [17,18]. A disadvantage of CMR FT compared to STE that may partly account for these differences is the fairly uniform water content and thus homogenous signal within myocardium on bSSFP sequences.…”
Section: Discussioncontrasting
confidence: 64%
“…Although there are multiple studies describing the strain characteristics of LVNC assessed by STE [15][16][17][18], CMR FT has some potential advantages that may provide a more accurate and reproducible assessment. The comparatively unrestricted access to multi-planar views and excellent contrast between the myocardium and blood pool allows reproducible imaging planes and clear boundary points for the measurement of myocardial strain [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies also showed impaired LV twist and the presence of rigid body rotation in NCCM but not in LVHT. A correlation between LV twist reduction in apical rotation and LV function was observed [ 77 ]. Table 5 shows an overview of different echocardiographic criteria.…”
Section: Diagnostic Criteriamentioning
confidence: 99%